2009
DOI: 10.1523/jneurosci.5030-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Delimited Coupling of TRPV1 and mGluR5 on Presynaptic Terminals of Nociceptive Neurons

Abstract: Transient receptor potential vanilloid subtype 1 (TRPV1) and metabotropic glutamate receptor 5 (mGluR5) located on peripheral sensory terminals have been shown to play critical roles in the transduction and modulation of pain sensation. To date, however, very little is known regarding the significance of functional expression of mGluR5 and TRPV1 on the central terminals of sensory neurons in the dorsal horn of the spinal cord. Here we show that TRPV1 on central presynaptic terminals is coupled to mGluR5 in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 55 publications
2
62
0
Order By: Relevance
“…However, in rat DRG neurons OAG-induced calcium signals have been ascribed to increased TRPV1 activity (18,55), indicating differential TRPV1 sensitivity to DAG in distinct cell lines. In DRG-derived F11 cells, we observed that accumulation of endogenous DAG and application of exogenous OAG induced Ca 2ϩ signals solely in F11-MRGPR-X1/TRPV1, but not in F11-MRGPR-X1 cells, indicating that DAG activates TRPV1 in F11 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, in rat DRG neurons OAG-induced calcium signals have been ascribed to increased TRPV1 activity (18,55), indicating differential TRPV1 sensitivity to DAG in distinct cell lines. In DRG-derived F11 cells, we observed that accumulation of endogenous DAG and application of exogenous OAG induced Ca 2ϩ signals solely in F11-MRGPR-X1/TRPV1, but not in F11-MRGPR-X1 cells, indicating that DAG activates TRPV1 in F11 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MRGPRX1 engaged TRPV1 via two distinct signaling pathways: sensitization took place via PKC-mediated phosphorylation of serine residues 502 and 800 of the channel, whereas direct TRPV1 activation relied on diacylglycerol binding to channel regions encompassing tyrosine 511 and phosphatidylinositol-3,4-bisphosphate (PIP 2 ) degradation. This multifaceted modulation of TRPV1 activity is unique among the GPCR superfamily (Chuang et al, 2001;Prescott and Julius, 2003;Woo et al, 2008;Kim et al, 2009;Solinski et al, 2012) and, thus, points to an important role of the TRPV1-MRGPRX1 regulatory axis in somatosensation.…”
Section: Ligandmentioning
confidence: 92%
“…Transient receptor potential vanilloid 1 channels also play a critical role in the transduction of pain sensation. They have recently been shown to be functionally coupled to mGlu5 receptors on presynaptic terminals of sensory neurons in the dorsal horn of the spinal cord (Kim et al, 2009). Accordingly, transient receptor potential vanilloid 1 is involved in pain behaviors induced by spinal mGlu5 receptor activation by the agonist DHPG and blocked by MPEP.…”
Section: A Allosteric Ligands For Group I Metabotropic Glutamate Recmentioning
confidence: 99%